Personal networks and urban socio-spatial fragmentation: the hypotheses of fragmentation - Furini, Luciano Antonio [UNESP]; Alves, Afonso Muzzo (Revues Org, 2021)
The specificity of the urban socio-spatial fragmentation process is configured to embrace other processes that already exist in our cities, characterizing its own dynamics. In this study, we seek to debate this theme from the analysis of the categories form, function, structure and process, with the results of the Maringa case study, city located in the state of Parana, Brazil. The methodology, based on the analysis of social and personal networks, allowed to characterize the patterns of urban practices and the results made it possible to identify the hypothesis of sociospatial networks, in the context of fragmentary logic.
Keywords: urban socio-spatial fragmentation; analysis of personal networks; city Maringa (PR)